2021
DOI: 10.1021/acs.est.0c08189
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of DMS and HOBr as a Sink for Marine DMS and an Inhibitor of Bromoform Formation

Abstract: Recently, we suggested that hypobromous acid (HOBr) is a sink for the marine volatile organic sulfur compound dimethyl sulfide (DMS). However, HOBr is also known to react with reactive moieties of dissolved organic matter (DOM) such as phenolic compounds to form bromoform (CHBr3) and other brominated compounds. The reaction between HOBr and DMS may thus compete with the reaction between HOBr and DOM. To study this potential competition, kinetic batch and diffusion-reactor experiments with DMS, HOBr, and DOM we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
0
7
1
Order By: Relevance
“…For example, a recent study identified the reaction of DMS with hypobromous acid as a potential marine DMS removal mechanism. 56 However, our study did not provide direct evidence of this pathway. Besides, we guess vertical mixing may serve as a potential sink of mixedlayer DMS.…”
Section: Modeled Photochemical Processescontrasting
confidence: 68%
See 1 more Smart Citation
“…For example, a recent study identified the reaction of DMS with hypobromous acid as a potential marine DMS removal mechanism. 56 However, our study did not provide direct evidence of this pathway. Besides, we guess vertical mixing may serve as a potential sink of mixedlayer DMS.…”
Section: Modeled Photochemical Processescontrasting
confidence: 68%
“…Unidentified DMS sinks within the mixed layer, which have not been considered in this study, may contribute to this discrepancy. For example, a recent study identified the reaction of DMS with hypobromous acid as a potential marine DMS removal mechanism . However, our study did not provide direct evidence of this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Isoprene could have reacted with H 2 O 2 in seawater as it does in acidic aerosols 26 . Besides, should dissolved 27 BrPOs from seaweeds or outer-membrane-bound 28 BrPOs from phytoplankton occur, they would have reacted with added H 2 O 2 to produce hypobromous acid (HOBr), a strong oxidant 29 that would further remove isoprene. Indeed, the addition of BrPO consumed isoprene because it produced HOBr by reaction with the naturally occurring H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, as we used environmentally relevant nitrate/DOS concentration ratios, the photo chemical reaction between nitrate and DOS in the culture experiment was similar to that under natural conditions. Similarly, previous research used environmentally relevant DMS/DOM concentration ratios to simulate the real marine environment to explore the reaction between DMS and hypobromous acid (Muller et al, 2021). Figure 3 presents the COS production profiles in surface seawater with/without cysteine and nitrate additions at room temperature.…”
Section: Effect Of Nitrate On Cos Production Under Simulated Sunlightmentioning
confidence: 99%